The cultural life of Bristol, 1640-1775 - Barry, J (1985)
Historians have become increasingly concerned with changes in urban provincial culture between the Civil War and the late eighteenth century, particularly as it has become clear that urban industrialization in the provinces depended heavily on a preceding period in which both the mentality and the trading infrastructure of ‘consumer society' were created. Renewed interest in extra-Parliamentary politics has also focused attention on the urban electorate and public opinion. Most of the research in these fields has, however, been carried out on a national scale, examining particular features of urban cultural life. The aim of this thesis is to test the assumptions and conclusions of recent historical work through a detailed analysis of one major city, emphasizing the inter-connections between cultural changes and their local significance. The approach adopted is essentially that of social rather than intellectual history, concentrating on the social circumstances which affected involvement in, and attitudes towards, cultural activity, rather than analysis of the changing styles and content of particular cultural practices. The first half of the thesis is concerned with the background to artistic and scientific activity, namely educational provision, the place of the printed word, and the nature of leisure and sociability, while the final chapter looks at the values associated with urban life, and their impact on political and religious behaviour. Therefore, although it concentrates on the 'culture' of literature, painting, music, drama, and intellectual research, the thesis attempts to ask broad questions in the social scientific tradition about their context and meaning. In doing so, this study is intended to redress the imbalance in current historiography. Recent work has mostly looked at urban life from outside, evaluating the economic or political ‘impact of towns! on national affairs. To the general dangers of 'Whiggishness' have been added specific assumptions which have encouraged the tendency to ignore the nature and impact of cultural change within the town. It has been assumed that a growing divergence of elite and popular culture, and the spread of metropolitan cultural practices and standards left the respectable inhabitants of provincial towns with little option but to follow the cultural changes pioneered by the landed and professional classes. Often the towns benefited economically by acting as regional entrepots for leisure and cultural activity by the gentry and pseudo-gentry, but they were subordinate both to their London suppliers and their genteel customers. The gradual re-establishment of political stability is thought to have followed the same pattern. Only with the establishment of an independent industrial base did a distinct urban provincial consciousness emerge, complete with new middle-class political aims and practices. Continued in thesis ...